2012
DOI: 10.4088/pcc.11m01209
|View full text |Cite
|
Sign up to set email alerts
|

Public Familiarity With the TermsSomatoform DisorderandFunctional Disorderin Germany

Abstract: Participants with a potential somatoform disorder did not differ in their familiarity ratings from others. We conclude that these diagnostic terms are probably not commonly used by physicians in routine clinical communication with patients suffering from unexplained medical symptoms. Future empirical research should investigate whether the currently proposed diagnosis complex somatic symptom disorder can solve current problems of acceptability, communication, and adequate treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Our recent results have shown that functional and somatoform symptoms are often associated with craniofacial pain (63.8% of patients) [2]. These symptoms include conditions that show no fi ndings in complementary exams and have no identifi able organic cause [5,6]. They were more frequent in patients having Temporomandibular Disorders (TMD), fi bromyalgia, and other non-neuropathic conditions [7,8], which can correspond to multimorbid states that often include gastrointestinal abnormalities and psychiatric disorders associated [9,10].…”
mentioning
confidence: 99%
“…Our recent results have shown that functional and somatoform symptoms are often associated with craniofacial pain (63.8% of patients) [2]. These symptoms include conditions that show no fi ndings in complementary exams and have no identifi able organic cause [5,6]. They were more frequent in patients having Temporomandibular Disorders (TMD), fi bromyalgia, and other non-neuropathic conditions [7,8], which can correspond to multimorbid states that often include gastrointestinal abnormalities and psychiatric disorders associated [9,10].…”
mentioning
confidence: 99%